Bullying victimisation, internalising symptoms, and conduct problems in South African children and adolescents: a longitudinal investigation. - Boyes, M; Bowes, L; Cluver, L; Ward, C; Badcock, N (Springer, 2014)
Bullying victimisation has been prospectively linked with mental health problems among children and adolescents in longitudinal studies in the developed world. However, research from the developing world, where adolescents face multiple risks to social and emotional development, has been limited by cross-sectional designs. This is the first longitudinal study of the psychological impacts of bullying victimisation in South Africa. The primary aim was to examine prospective relationships between bullying victimisation and internalising and externalising symptoms in South African youth. Secondary aims were to examine gender and age-related differences in experiences of bullying victimisation. Children and adolescents (10-17 years, 57 % female, n = 3,515) from high HIV-prevalent (>30 %) communities in South Africa were interviewed and followed-up 1 year later (97 % retention). Census enumeration areas were randomly selected from urban and rural sites in two provinces and door-to-door sampling included all households with a resident child/adolescent. Exposure to multiple experiences of bullying victimisation at baseline predicted internalising symptoms and conduct problems 1 year later. Additionally, baseline mental health scores predicted later bullying victimisation, demonstrating bi-directionality of relationships between bullying victimisation and mental health outcomes in this sample. Expected gender differences in physical, verbal, and relational bullying victimisation were evident and predicted declines in bullying victimisation over time were observed. In the developed world, school-based anti-bullying programmes have been shown to be effective in reducing bullying and victimisation. Anti-bullying programmes should be implemented and rigorously evaluated in South Africa, as this may promote improved mental health among South African children and adolescents.